Aiming for elimination: Outcomes of a consultation pathway supporting regional general practitioners to prescribe direct‐acting antiviral therapy for hepatitis C. Issue 9 (8th May 2018) - Wade, A. J.; McCormack, A.; Roder, C.; McDonald, K.; Davies, M.; Scott, N.; Wardrop, M.; Athan, E.; Hellard, M. E.
Summary: To increase access to treatment, the Australian government enabled general practitioners (GPs) to prescribe direct‐acting antivirals (DAAs) to treat hepatitis C virus (HCV)— in consultation with a specialist if inexperienced in HCV management. This study describes the establishment and outcomes of a remote consultation pathway supporting GPs to treat HCV. Key stakeholders from primary and tertiary healthcare services in the Barwon South Western region developed and implemented an HCV remote consultation pathway. Pharmaceutical Benefits Schedule prescription data were used to evaluate GP DAA prescription 12 months pre‐and post‐ pathway implementation. A retrospective review of patients referred for remote consultation for 12 months post‐ pathway inception was undertaken to determine the care cascade. HCV treatment initiation by GPs increased after implementation of the remote consultation pathway. In the 12‐month study period, 74 GPs referred 169 people for remote consultation; 114 (67%) were approved for GP DAA treatment; 48 (28%) were referred for specialist assessment. In total, 119 (71%) patients commenced DAA; 69 were eligible for SVR12 assessment. Post‐treatment HCV RNA data were available for 52 (75%) people; 37 achieved SVR12; 15 achieved SVR ranging from week 5 to 11 post‐treatment. No treatment failure was detected. Collaborative development and implementation of a remote consultation pathway has engaged regional GPs in managing HCV. Follow‐up post‐treatment could be improved; however, no treatment failure has been documented. To eliminate HCV as a public health threat, it is vital that specialists support GPs to prescribe DAA.